PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MELALUI LOYALITAS SEBAGAI VARIABEL INTERVENING PADA CV. NETRAL JAYA DI KECAMATAN PURWOREJO KOTA PASURUAN - Asiyah, Putri; Fibriyani, Vita; Erwantiningsih, Eni (Yayasan Education and Social Center, 2024)
Success in developing a business is determined by the performance of both the company and its employees. This research aims to determine the influence of motivation and work discipline on employee performance through loyalty as an intervening variable in CV. Netral Jaya Pasuruan City. This research is a quantitative descriptive study using census sampling techniques. Data analysis techniques use validation tests, reliability, classical assumptions, hypotheses, path analysis and sobel tests. The results of this research show that (1) motivation and discipline have a simultaneous effect on loyalty, motivation and good discipline, so employee performance increases, (2) motivation and discipline have a simultaneous effect, good motivation and discipline then employee performance increases, (3) motivation does not have a significant effect on loyalty, company leaders provide good service and facilities to employees, (4) discipline has a significant effect on loyalty, good discipline increases employee loyalty, (5) motivation has a significant effect on performance, good motivation increases employee performance , (6) discipline has a significant effect on performance, good discipline increases employee performance, (7) loyalty does not have a significant effect on performance, company leaders provide good service to employees, (8) loyalty is able to mediate motivation on performance, good motivation gaining a sense of loyalty produces good performance, (9) loyalty is able to mediate discipline on performance, good discipline produces a sense of loyalty resulting in good performance